Evaluation of advanced lines of Brassica carinata for drought response - Preeti Lohani; Usha Pant; Rashmi; Sneha Adhikari; Harshita Negi; Ram Bhajan (Journal of Oilseed Brassica, 2026)
Ethiopean mustard (Brassica carinata) is one of the six commercially important Brassica species and is considered to betolerant to drought, diseases and insect-pest so better adapted to problematic areas. Drought is an abiotic stress whichhampers the yield and productivity of crop. The present investigation aimed at evaluation of advanced lines of Brassicacarinata for drought response. The experiment was conducted at G.B. Pant University of Agriculture and Technology,Pantnagar, India. The experimental material consisted of thirty seven advanced lines of B. carinata along with threechecks, two of B. carinata cultivar Pusa Swarnim and Kiran and one of B. juncea cultivar Giriraj. Relative leaf watercontent, Water saturation deficit and electrolyte leakage were taken as indicators of drought response. ANOVA revealedsignificant differences for all three drought related parameters among genotypes. Kiran showed excellent capacity tomanage the stress condition through high relative leaf water content, low water saturation deficit and moderate electrolyteleakage. 30 lines showed significant better response in relation to electrolyte leakage than Kiran. Indian mustard checkGiriraj showed poorest response towards the stress condition. For other parameters lines showed intermediate responsetowards drought. The genotypes identified better for stress condition after confirmation can be further used either asone of the parent for hybridization programme targeted for stress condition. Therefore, with better insight of exploitablevariability maximum gain in form of potential cultivar can be achieved to meet out future challenges